KAJIAN LABEL KEMASAN MAKANAN RINGAN UMKM DI TIGA KELURAHAN KOTA BANDUNG - NINA NURVIANA (Serat Rupa: Journal of Design, 2016)
Research about packaging label who produced by UMKM is rarely discussed, eventhough apart from its economical fact, this business contribute large sum of Indonesia’s Domestic Bruto Product. Small local business sector is proven to have endurance against economy crisis which occurs frequently in Indonesia, and have benefit in helping government to tackle unemployment issues.UMKM product like chips and crackers distributed to satisfy low income  market,however with the slightly minimum profit margin, they must have  fulfill governments policy to put label on its packaging as information medium and brand identity for the consumers.Packaging label of various chips and crackers research shall implement with qualitative approach, in purpose for identifying packaging’s graphic on label. Plastic package possess flexibility in many aspect, from primary, secondary and tertiary function has their own advantage, convenience logistic and possibility to reach remote areas. Majority of products label designed to be symmetrical layout with border and basically the design always similarity between products to another. The utilization of typography and color on the label already decently has informative, the point to be improved is the clarity& neatness. Traditional  local words always used ‘Sugih’, ‘Bagja’ or ‘Sari Rasa’ are advisable to be maintained to preserve local taste.Keyword:  label;  packaging; snack; typography; UMKM